Water‐in‐oleogel emulsion based on γ‐oryzanol and phytosterol mixtures: Challenges and its potential use for the delivery of bioactives. (30th July 2022) - Pinto, Tiago C.; Martins, Artur J.; Pastrana, Lorenzo; Pereira, Maria C.; Cerqueira, Miguel A.
Abstract: The present work aimed at developing a novel water‐in‐oleogel emulsion using a mixture of γ‐oryzanol and phytosterols as gelator. The gelator network was severely affected by the presence of water, with single β‐sitosterol crystals being the main contributors to the self‐standing ability of the emulsions. X‐ray analyses have shown sharp crystallographic reflections for anhydrous and hemihydrated β‐sitosterol crystals, independently of the gelator concentrations and water‐in‐oleogel ratios. The samples with higher water content have shown additional reflections that could be traced back to monohydrated β‐sitosterol crystals, but these were not present after 7 days. The rheological analysis has revealed the impact of the emulsion composition on their strength. Foreseeing their use for the co‐delivery of bioactive compounds, we added β‐carotene and epigallocatechin gallate to the emulsions. We confirmed their viability toward the incorporation of bioactives in their free‐form, constituting a proof of concept for the fortification of lipid‐rich foods with both oil and water‐soluble bioactive compounds.